Hyperforin, an Anti-Inflammatory Constituent from St. John's Wort, Inhibits Microsomal Prostaglandin E2 Synthase-1 and Suppresses Prostaglandin E2 Formation in vivo - Koeberle, Andreas; Rossi, Antonietta; Bauer, Julia; Dehm, Friederike; Verotta, Luisella; Northoff, Hinnak; Sautebin, Lidia; Werz, Oliver (Frontiers in Pharmacology, 2011)
The acylphloroglucinol hyperforin (Hyp) from St. John’s wort possesses anti-inflammatory and anti-carcinogenic properties which were ascribed among others to the inhibition of 5-lipoxygenase. Here, we investigated whether Hyp also interferes with prostanoid generation in biological systems, particularly with key enzymes participating in prostaglandin (PG)E2 biosynthesis, i.e., cyclooxygenases (COX)-1/2 and microsomal PGE2 synthase (mPGES)-1 which play key roles in inflammation and tumorigenesis. Similar to the mPGES-1 inhibitors MK-886 and MD-52, Hyp significantly suppressed PGE2 formation in whole blood assays starting at 0.03 to 1 µM, whereas the concomitant generation of COX-derived 12(S)-hydroxy-5-cis-8,10-trans-hepta¬deca¬trienoic acid, thromboxane B2, and 6-keto PGF1α was not significantly suppressed up to 30 µM. In cell-free assays, Hyp efficiently blocked the conversion of PGH2 to PGE2 mediated by mPGES-1 (IC50 = 1 µM), and isolated COX enzymes were not (COX-2) or hardly (COX-1) suppressed. Intraperitoneal (i.p.) administration of Hyp (4 mg kg-1) to rats impaired exudate volume and leukocyte numbers in carrageenan-induced pleurisy associated with reduced PGE2 levels, and Hyp (given i.p.) inhibited carrageenan-induced mouse paw edema formation (ED50 = 1 mg kg-1) being superior over indomethacin (ED50 = 5 mg kg-1). We conclude that the suppression of PGE2 biosynthesis in vitro and in vivo by acting on mPGES-1 critically contributes to the anti-inflammatory efficiency of Hyp.